Hisab Dan Rukyat Dalam Penentuan Awal Bulan Qamariyah Di Indonesia Perspektif Hadis - Ahmad Muslih Haryanto (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2023)
The problem of determining the beginning of the Qomariyah month using the hisab and rukyat methods has been controversial in Indonesia for a long time. This is caused by differences in views. The aim of this research is to provide an understanding regarding the methods of reckoning and rukyat from the perspective of hadith in determining the beginning of the month of Qomariyah. This research uses a library research approach with qualitative analysis methods based on data collected from hadiths related to determining the beginning of the month of Qomariyah. The analysis in this research uses content analysis to draw conclusions. The results of this research show that when referring to the hadith, when referring to the hadith, there is khilafiyah in the interpretation. This is what happens in Indonesia, in determining the beginning of the Qomariyah month, there is a difference caused by the meaning of the hadith text itself. Therefore, a textual understanding of the hadith is necessary, so that the interpretation of its meaning can be fully understood. Thus, in dealing with differences that arise, an attitude of mutual respect for each other is needed. So that the existing differences do not give rise to sentiment and division between Muslims in Indonesia.